Forced convection of ferrofluids in a vented cavity with a rotating cylinder - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier France-Editions Scientifiques Medicales Elsevier, 2014)
In this study, numerical investigation of the forced convection of ferrofluid in a square cavity with ventilation ports in the presence of an adiabatic rotating cylinder is carried out. The governing equations are solved with a finite element based solver. The effects of Reynolds number (20 <= Re <= 400), angular rotational speed of the cylinder (-500 <= Omega <= 500), strength and location of the magnetic dipole (0 <= gamma <= 250), (0.2 <= a <= 0.8, -0.8 <= b <= -0.2) on the flow and thermal fields are numerically studied. It is observed that the length and size of the recirculation zones can be condtrolled with magnetic dipole strength and angular rotational speed of the cylinder. When the magnetic dipole is closer to the bottom wall of the cavity, flow is accelerated towards the bottom wall with larger influence area. The increasing values of the angular rotational speed of the cylinder in the clockwise direction enhance the heat transfer. (C) 2014 Elsevier Masson SAS. All rights reserved.
Keywords: Magnetic dipole; Rotating cylinder; Vented cavity; Finite element method